INVESTMENT POTENTIAL AND THE EFFECT OF FINANCIAL RATIOS STOCK RETURN IN MINING SECTOR IN ENVIRONMENT PRO STOCK INDEX AND SHARIA - Heni Istianawati; Abdul Kohar Irwanto,; Mukhamad Najib (Pusbindiklat - LIPI, 2015)
Investment is an investing activity on a company of aimed to obtain the return. One of the interesting investmentsfor investors is investing in the mining sector because of large amount of return obtained in a short time.Before choosing which stocks to be invested in the mining companies, investors need to look at the companyperformance to avoid the risk. The purposes of this study are to examine the investment potential and analyze theinfluence of financial ratios (CR, DER, EPS, ROE, TATO, ROA, PER, NPM) on stock returns in the mining sector.The object of this research is mining companies who are listed on index SRI-Kehati and Jakarta Islamic Index(JII) period 2010–2013 consistently. The method used was descriptive analysis to calculate Tobin‘s Q score tolook at potential investments. Panel data regression analysis was conducted to see the effect of financial ratios tostock return. The results show that PTBA and MEDC have high investment potential from 2010–2013. Becausethe company’s Tobin‘s Q score acquired above 1 for four consecutive years, while the explanatory variables havea positive and significant effect on stock returns is CR, EPS, ROA, and PER. PTBA is the highest average score ofCR, EPS, ROA, and PER compared to the other mining companies. Therefore, PTBA is the best choice of investmentfor investors, specifically in the mining sector.